Becoming a manager - Hill, Linda A. (Harvard Business School Press, 2019)
In this timeless, indispensable book, Harvard Business School professor and leadership guru Linda Hill traces the experiences of nineteen new managers over the course of their first year in the role. She reveals the complexity of the transition, highlighting the expectations of these managers, their subordinates, and their superiors. We hear the new managers describe how they reframed their understanding of their roles and responsibilities, how they learned to build effective cross-functional work relationships, how and when they used individual and organizational resources, and how they learned to cope with the inevitable stresses of leadership